Cover Feature: Reliable Functionalization of 5, 6‐Fused Bicyclic N‐Heterocycles Pyrazolopyrimidines and Imidazopyridazines via Zinc and Magnesium Organometallics (Chem. Eur. J. 33/2022). Issue 33 (19th May 2022) - Kumar Rout, Saroj; Kastrati, Agonist; Jangra, Harish; Schwärzer, Kuno; Sunagatullina, Alisa S.; Garny, Maximilien; Lima, Fabio; Brocklehurst, Cara E.; Karaghiosoff, Konstantin; Zipse, Hendrik; Knochel, Paul
Abstract : Two fused N‐heterocyclic scaffolds were selectively functionalized giving access to novel pharmaceutical targets that offer a better life to the whole world. More information can be found in the Research Article by P. Knochel and co‐workers (DOI: 10.1002/chem.202200733 ).